Understanding transparency in UK defence management. (22nd April 2019) - Thompson, Gabriela; Louth, John
Abstract: Transparency has become a key word in UK defence management, but its meaning is unclear; there are those that argue that it is too abstract to be implemented in its true essence, whilst others argue that it is inherently incompatible with the New Public Management Model which dominates public sector management today. Through observing the way individuals operationalise the concept in the defence community, we attempt to illustrate what transparency seems to mean in practice by focussing on how it is understood and recognising the impact it has and is expected to have.